Replacement of 24-h creatinine clearance by 2-h creatinine clearance in intensive care unit patients: a single-center study. - Herrera-Gutiérrez, Manuel Enrique; Seller Pérez, Gemma Luisa; Banderas Bravo, Esther; Muñoz Bono, Javier; Lebrón Gallardo, Miguel; Fernández Ortega, Juan Francisco (Springer Nature, 2007)
Objective: To estimate the usefulness of 2-h creatinine clearance (CrCl) in the ICU and define variables that may reduce agreement. Design: Prospective study. Setting: Polyvalent ICU of a university hospital. Patients: 359 patients. Interventions: We compared 24-h CrCl (CrCl-24h), as the standard measure, with 2-h CrCl (CrCl-2h) (at the start of the period) and the Cockroft-Gault equation (Ck-G). Measurements and results: The 2-h sample was lost in two patients (0.6%) and the 24-h sample was lost in 50 patients (13.9%). The mean Ck-G was 87.4+/-3.05, with CrCl-2h 109.2+/-4.46 and CrCl-24h 100.9+/-4.21 ml/min/1.73 m2 (r2 of 0.88 for CrCl-2h and 0.84 for Ck-G). The differences from ClCr-24h were 21.8+/-3.3 (p<0.001) for the Ck-G and 8.3+/-2.6 (p<0.05) for CrCl-2h (p<0.05). In the subgroup of patients with CrCl-24h<100 ml/min/1.73 m2, the CrCl-24h value was 52.9+/-2.71 vs. 51.6+/-2.14 for CrCl-2h (p=ns) and 57.6+/-2.56 (p<0.001) for the Ck-G. Patients with CrCl<100 ml/min only showed variability in hyperglycemia during the 24-h period. Conclusions: In intensive care patients, 24-h CrCl results in a large proportion of non-valid determinations, even under conditions of close monitoring. Two-hour CrCl is an adequate substitute, even in patients who are unstable or who have irregular diuresis where a 24-h collection is impossible. The Cockroft-Gault equation seems less useful in this setting.
Keywords: Riñones - Lesiones y heridas; Cuidados intensivos; Creatina; Creatine / blood; Creatine / metabolism*; Kidney / injuries; Critical care